Metabolomic profiling of finger millet: unlocking the secrets of a nutritious staple food - Gupta, Vishal; Sharma, Mahima; Gupta, Sushil Kumar; Javeria, Shaily; Amin, Zakir; Ashraf, Suhail; Khan, Javed Masood; Udavant, Rajesh N. (Frontiers in Plant Science, 2025)
IntroductionFinger millet (Eleusine coracana) is gaining increasing recognition as a functional food and a promising source of nutraceuticals for mitigating metabolic disorders, owing to its abundance of bioactive compounds. Despite its nutritional and therapeutic potential, comprehensive metabolomic profiling of its primary and secondary metabolites remains limited. This study aimed to perform an in-depth metabolomic analysis of finger millet landraces cultivated in the temperate region of Padder Valley, District Kishtwar, Union Territory of Jammu and Kashmir, and to assess the therapeutic relevance of these metabolites in preventing metabolic diseases.MethodsComprehensive phytochemical profiling was conducted using liquid chromatography coupled with high-resolution tandem mass spectrometry (LC-HRMS/MS) to identify and characterize primary and secondary metabolites in finger millet grains. Inductively coupled plasma mass spectrometry (ICP-MS) was employed to quantify macro- and microelemental contents.ResultsMetabolomic analysis identified a total of 50 primary metabolites, including derivatives of amino acids, fatty acids, and carbohydrates such as dehydroascorbic acid, niacin, xanthine, orotic acid, nicotinuric acid, gluconic acid, propionic acid, decanoic acid, and palmitic acid. Additionally, 135 secondary metabolites were characterized, encompassing heterocyclic compounds, phenolics, flavonoids, alkaloids, and terpenes such as 4-hydroxycyclohexylcarboxylic acid, 2-furoic acid, methyl cinnamate, mesitol, 4-hydroxybenzoic acid, heptalactone, viburtinal, and geranic acid. Elemental analysis revealed the presence of 10 macro- and microelements, with magnesium (Mg), calcium (Ca), potassium (K), and phosphorus (P) being the most abundant.DiscussionThe comprehensive metabolite profiling demonstrates that finger millet is a rich source of bioactive primary and secondary compounds with potential therapeutic benefits. The diversity of metabolites and essential minerals highlights its value as a functional food ingredient for the prevention and management of metabolic disorders. These findings provide a biochemical basis for the development of value-added nutraceutical products derived from finger millet landraces.